Mechanism Analysis of Strategy Choice of Bankruptcy Reorganization Participants under Government Incentive Mechanism - Danyu Zhao; Li Song (Complexity)
This study constructs an evolutionary game model of government, creditors, investors, and enterprises participating in bankruptcy reorganization, analyzes the strategy selection mechanism of the four parties under the government incentive mechanism, systematically analyzes the strategy selection process of each participant, discusses the effectiveness of government incentives in promoting the bankruptcy reorganization process, and finds out the stable point in the replication dynamic system. Finally, MATLAB 2018 software is used to numerically model the influence of key elements of the system. The research shows that under the government’s incentive mechanism, creditors participate in bankruptcy reorganization in the form of debt-to-equity swaps, investors participate in bankruptcy reorganization in the form of providing high-quality assets, and enterprises participate in bankruptcy reorganization in the form of reform and transformation which is a stable strategy to replicate the dynamic system; the strategy of the enterprises will affect the strategy choice of creditors and investors; the completion of bankruptcy reorganization is inseparable from the government’s incentives, and the government’s strategy will directly affect the strategic choice of enterprises; and the government’s support and constraint strength satisfy the following quantitative relationship: when M1>S3–C1 and L1>B1–C1, it can better promote the bankruptcy and reorganization process.